Molecular effects of copper on the reproductive system of mytilus galloprovincialis. Issue 10 (22nd January 2019) - Lettieri, Gennaro; Mollo, Velia; Ambrosino, Alessia; Caccavale, Filomena; Troisi, Jacopo; Febbraio, Ferdinando; Piscopo, Marina
Abstract : This study aims to assess the effects induced by 24 hr exposure to a subtoxic copper concentration on the reproductive system (gonads, spermatozoa, and protamine‐like [PL] proteins) of Mytilus galloprovincialis . Inductively coupled plasma–mass spectrometry indicated accumulation of this metal in gonads, spermatozoa, and PL proteins of exposed mussels. Further, real‐time polymerase chain reaction analyses showed altered expression levels of mt10 and PL proteins genes in spermatozoa and gonads, respectively, of exposed mussels. Protamine‐like proteins, which represent the main basic component of sperm chromatin of this organism, showed a higher DNA binding affinity and a different DNA binding mode in exposed mussels. Moreover, an increased amount of NaCl was required for the release from sperm nuclei of PL‐III, the main PL protein component. Finally, PL proteins extracted from exposed mussels promoted DNA oxidative damage in the presence of H2 O2. These results demonstrate that the tolerable copper amount could also affect the properties of PL proteins and determine the negative effects on the reproductive system of this organism. These analyses could be useful to develop quick and efficient chromatin‐based genotoxicity tests for pollution biomonitoring programs. Abstract : Exposure of mytilus galloprovincialis to 15 µM copper chloride produced copper accumulation in gonads, spermatozoa, and protamine‐like (PL) proteins, increasing the expression levels of genes coding for PL proteins in gonads. Moreover, it increased the DNA binding affinity and changed the DNA binding mode of PL proteins. Finally, PL proteins from exposed mussels promoted DNA oxidative damage. These lines of evidence give new insights into the copper toxicity mechanisms on the reproductive system of marine organisms.